Unusual symptom of abdominal pain in imperforate hymen mimicking acute appendicitis: A case report - Supangat; Achmad Ilham Tohari; Muhammad Yuda Nugraha; Elly Nurus Sakinah; Salsabila Imtiyazfauz; Nabil Athoillah; Muhammad Rijal Fahrudin Hidayat (Elsevier, 2022)
Imperforate hymen (IH) is a female genital tract abnormality in which the hymen entirely blocks the vaginal entrance. Because of its low incidence, nonspecific symptoms, and poor physical examination, IH is frequently ignored or delayed in diagnosis. Here we report a case of an unusual symptom of IH like constipation along with abdominal pain mimicking appendicitis with 6 points Alvarado score that causes delayed diagnosis of IH. A 12-year-old girl presented with continuous abdominal pain, unable to defecate for three days, and dysuria. The patient was consulted to several departments due to unspecific symptoms. The initial diagnosis for the patient are constipation and suspect appendicitis until the patient consulted to a pediatric surgeon that successfully diagnose IH. Without proper management and timely treatment, IH may cause morbidity. This report points out the importance to assess IH's symptoms in female adolescence who experience abdominal pain to avoid delayed diagnosis, give the correct treatment of IH, and give the key findings to distinguish IH and acute appendicitis.